In vivo three dimensional dual wavelength photoacoustic tomography imaging of the far red fluorescent protein E2-Crimson expressed in adult zebrafish - Liu, Mengyang (Optical Society of America, 2013)
For the first time the far red fluorescent protein (FP) E2-Crimson genetically expressed in the exocrine pancreas of adult zebrafish has been non-invasively mapped in 3D in vivo using photoacoustic tomography (PAT). The distribution of E2-Crimson in the exocrine pancreas acquired by PAT was confirmed using epifluorescence imaging and histology, with optical coherence tomography (OCT) providing complementary structural information. This work demonstrates the depth advantage of PAT to resolve FP in an animal model and establishes the value of E2-Crimson for PAT studies of transgenic models, laying the foundation for future longitudinal studies of the zebrafish as a model of diseases affecting inner organs.